The impact of the pandemic on the radio business in West Java-Indonesia - Ellang Gantoni Malik (Proceeding of the International Conference on Family Business and Entrepreneurship, 2022)
The era of disruption and pandemic has changed the economic climate and the calculation of profits for various business sectors, including the service, trade, and manufacturing sectors. in 2020 it is almost certain that there will be a change in the calculation of financial targets both in terms of net present value and internal rate return, as well as in 2021, where profits are under great pressure. The service industry sector is one of the sectors experiencing deep pressure, especially the radio mass media business. Mass media including broadcast radio institutionally has two different sides, firstly commercial and profit-oriented as a business, and secondly social and idealism. The COVID-19 pandemic has been going on for about 17 months and has had a bad impact. as well as the financial impact experienced by radio media, most radio broadcasting media experienced a decrease in income in the range of 50% - 70% of normal conditions. Such conditions require radio media to adapt to the situation by rationalization and/or convergence, both in terms of business and social functions to survive. the steps taken are reducing broadcast hours, reducing the number of employees, and other efficiencies. there are even some who stop radio media business activities so that they do not carry out activities at all. The study uses financial analysis, data in the form of annual financial statements of income, in addition to financial statement data, direct interviews with decision-makers are carried out.